FERRORESONANCE AND SATURATION EFFECTS IN TRANSFORMERS: A FIELD-CIRCUIT APPROACH (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2026)
Ferroresonance is a complex, nonlinear oscillatory phenomenon in power systems that poses significant risks to insulation and equipment integrity due to sustained overvoltages and overcurrents. This paper presents a detailed time-domain investigation of ferroresonant modes in a 1 kVA single-phase transformer using a coupled field-circuit approach within ANSYS Electronics Desktop. By integrating the nonlinear magnetic properties of the M400-50A electrical steel core with an external capacitive network, the study accurately reproduces the "jump resonance" bifurcation. Simulation results reveal that under specific capacitive grading conditions, the transformer transitions into a high-energy fundamental mode (Period-1) oscillation. Finite Element Analysis (FEA) visualizes the physical mechanism driving these transients. Vector field analysis highlights the localized current density spikes in the primary windings, and their corresponding instantaneous core losses. The phase-plane representation and Poincaré maps are also used to rigorously examine the stability of the ferroresonant mode. These findings underscore the necessity of detailed electromagnetic modeling to predict the thermal and mechanical stresses associated with this phenomenon.
Keywords: Ferroresonance; Finite element analysis (FEA); Coupled field circuit simulation; Magnetic saturation; Poincaré map; Transformer; Nonlinear dynamics; Jump resonance; Subharmonic ferroresonance; Period-3 oscillation